Links Between Environmental Condition and Integrated Coastal Management Sustainability - Christie, Patrick; White, Alan T.; Stockwell, Brian; Jadloc, Renato Claro (Silliman Journal, 2022)
Integrated coastal management (ICM) is practiced throughout Asia with the support of millions of dollars. Unfortunately, many management regimes are not sustained beyond project termination and withdrawal of external technical and financial assistance. This study reports on the impacts of 1CM on coral reefs and the hypothesized links between changes in coral reef conditions due to such management regimes and management process sustainability. The study demonstrates that ICM has had positive impacts on coral reefs at one of two study sites in the Philippines. 1CM commonly utilizes marine protected areas (MPAs) as a management tool. The MPAs in Mabini are actively managed and have improved fish diversity and abundance. However, these MPAs are contested and at risk of collapse due to conflicts between fishing and tourism constituencies. The second site is without MPAs (Bais Bay) despite considerable investment of time and funding. The environmental condition appears to have stabilized in Bais Bay, but this condition is not readily attributable to ICM. An analysis of interviews suggests that the condition in the environment is not directly linked to ICM process sustainability as measured by whether stakeholders are motivated to support or participate in ICM over time. Rather, each stakeholder is motivated by the extent to which the particular ICM process agrees with their worldview or helps them meet social and economic goals. The condition of the environment is important to diverse stakeholder groups, but for different reasons. This paper is part of a larger research project, the ICM sustainability research project, investigating factors impacting ICM process sustainability in the Philippines and Indonesia.